Experimental paracoccidioidomycosis of the Syrian hamster: fungicidal activity and production of inflammatory cytokines by macrophages - Parise-Fortes, M. R.; da Silva, MFP; Sugizaki, M. F.; Defaveri, J.; Montenegro, M. R.; Soares, AMVC; Peracoli, MTS (B I O S Scientific Publishers Ltd, 2000)
Phagocytic cells play an important role in nonspecific resistance to fungal infection by mediating an inflammatory response and by a direct fungicidal action. In this study, the functional activity of peritoneal macrophages obtained from hamsters experimentally infected with strain Pb18 of Paracoccidioides brasiliensis was evaluated during 16 weeks of infection. The results showed that macrophages had a higher spreading ability associated with increased production of tumor necrosis factor alpha (TNF-alpha) and enhanced fungicidal activity during the early periods of infection. TNF-alpha levels remained elevated during all periods studied, while low levels of interleukin-1 beta (IL-1 beta) were produced during the infection. A necrotic area with dead fungi was observed at the inoculation site and the infection disseminated only to liver and lymph nodes in a few animals. These results suggest that during the early stages of infection with P. brasiliensis, macrophage activation by the high levels of TNF-alpha limited fungal dissemination. In contrast, in the later stages of infection, high levels of TNF-alpha were observed while the fungicidal activity of macrophages was lower and the animals presented loss of vitality resulting in their death. These observations suggest a complex role of TNF-alpha in experimental paracoccidioidomycosis of Syrian hamsters, involving not only resistance but also pathogenesis.
Keywords: hamsters; interleukin-1; paracoccidioidomycosis; tumor necrosis factor